Predictive Diagnostics of Risk Factors for the Development of Sarcopenia in Early Patients with Type 2 Diabetes - Yu. G. Samoilova; M. V. Matveeva; E. A. Khoroshunova; D. V. Podchinenova; Ya. L. Yakimova (SINAPS LLC, 2024)
Objective. Materials and methods: 82 patients with type 2 diabetes mellitus participated, which were divided into 2 groups: probable sarcopenia and comparison groups. Conducted: questionnaire surveys (Health Status Survey (SF-36)), Sarcopenia quality and life assessment (SarQoL)), strength, assistance with walking, getting up from a chair, climbing stairs and falling - Strength, Assisted walking, getting up from a chair, Climbing stairs and Falls (SARC-F)), assessment of walking speed and physical activity, carpal dynamometry, bioimpedancemetry, analysis of laboratory parameters. Results: the difference between the conducted questionnaires is statistically insignificant. According to bioimpedansometry, obesity of the 1st degree was recorded in the lesions. In the group with presarcopenia, the main decrease in body composition parameters decreases. In addition, in the main group, the rate of intake is reduced, and decompensation of carbohydrate and lipid metabolism occurs. Differences were considered significant at p < 0.05. Conclusion. Dynamometry and bioimpedance can be used for primary screening of sarcopenia in patients with type 2 diabetes. Maintaining the main indicators of glycemia, correction of dyslipidemia, compensation for obesity D and hypocalcemia of obesity in muscle mass and mass.